Korelasi Sistem Linguistik dengan Psikologi Intuitif dalam Membangun Karkter Anak - Abdul Munib; Subaidi Qomar (Peneliti.net, 2022)
The study of psychology is an interesting study. More specifically is psychology as a medium of character formation. The focus of this research is to try to see how the linguistic system relates to intuitive psychology in shaping character. There are several aspects as the object of this research, First, the system and structure of the language. Second, the theoretical concepts of psychology and linguistics. Third, the correlation of the linguistic system to psychology in forming abak character. As for the research approach, namely the study of literature (library research) examining various problems to answer the problems studied either through books, articles, journals and so on. The conclusion in this research is that intuitive linguistic and psychological systems have an essential role in shaping character because language is a verbal tool in communicating with other humans.